In vivo immunomodulation and lipid peroxidation activities contributed to chemoprevention effects of fermented mung bean against breast cancer - Yeap, Swee Keong; Mohd Yusof, Hamidah; Mohamad, Nurul Elyani; Beh, Boon Kee; Ho, Wan Yong; Mohd Ali, Norlaily; Mohammed Alitheen, Noorjahan Banu; Koh, Soo Peng; Long, Kamariah (Hindawi Publishing Corporation, 2013)
Mung bean has been reported to have antioxidant, cytotoxic, and immunomodulatory effects in vitro. Fermented products are reported to have enhanced immunomodulation and cancer chemopreventive effects. In this study, fermented mung bean treatments in vivo were studied by monitoring tumor development, spleen immunity, serum cytokine (interleukin 2 and interferon gamma) levels, and spleen/tumor antioxidant levels after injection with low and high risk 4T1 breast cancer cells. Pretreatment with fermented mung bean was associated with delayed tumor formation in low risk mice. Furthermore, this treatment was connected with higher serum anticancer cytokine levels, spleen T cell populations, splenocyte cytotoxicity, and spleen/tumor antioxidant levels. Histopathological evaluation of fermented mung bean treated tumor revealed lower event of mitotic division. On the other hand, antioxidant and nitric oxide levels that were significantly increased in the untreated mice were inhibited in the fermented mung bean treated groups. These results suggested that fermented mung bean has potential cancer chemoprevention effects through the stimulation of immunity, lipid peroxidation, and anti-inflammation.